Analisa Sistem Pelumas Menggunakan Metode FMEA Guna Mengetahui Kegagalan Sistem - Sabilil Huda Al Hakiki; Dwisetiono Dwisetiono (Departemen Teknik Kelautan Universitas Hasanuddin, 2021)
Failure in a component in the lubricant system will have an impact on the operation so a review is needed to overcome the failure of each component and the maintenance of components based on the level of risk. The creation of a risk-based treatment analysis with the FMEA method has several steps that describe the identification and evaluation of the system, process and treatment to determine the treatment strategy resulting from the method. Failure Mode and Effect Analysis (FMEA) is a method of evaluating risks in the system. FMEA can evaluate and analyze components in a system so as to minimize the risk or effect of a failure rate as a method of supporting performance assessment on a system. The use of FMEA methods other than in industrial machinery is widely used also to analyze preventive maintenance planning on ship machines. As a result, the FMEA method can identify the priority of the highest ration stainer component rpn value (Risk Priority Number) compared to other components. This study to determine the failure of each component of the lubricant system in the diesel engine and choose the right type of maintenance for the components. The benefits of knowing the failure and koponent maintenance of the lubricant system will provide benefits to the ship in terms of maintenance..